Parallel Worlds - Michio Kaku (Penguin Group, 2006)
MICHIO KAKU is the Henry Semat Professor of Theoretical Physics at the Graduate Center of the City University of New York. He is the author of several widely acclaimed books, including Visions, Beyond Einstein, and Hyperspace, which was named one of the best science books of the year by the New York Times and the Washington Post. He hosts a nationally syndicated radio science program and has appeared on such national television shows as Nightline, 60 Minutes, Good Morning America, and Larry King Live.
Keywords: Astronomy